Factors Affecting User Satisfaction of SISKEUDES in Village Financial Management - Bustamin, Fitri Yanti; Wardhani, Rulyanti Susi; Yanto, Yanto (LPPM STIE Krakatau, 2025)
Purpose: This study aims to examine the effects of perceived usefulness, perceived ease of use, information quality, and system quality on user satisfaction with the SISKEUDES application among village officials in South Bangka Regency, where its mandatory implementation has not yet fully optimized user satisfaction. Methodology/approach:. Methodology/approach: This study employed a quantitative approach using a survey method by distributing questionnaires to 69 village officials who used SISKEUDES. Data were analyzed using multiple linear regression with statistical software, including data quality tests and classical assumption tests. Results/findings:. Results/Findings: The results indicate that perceived usefulness, perceived ease of use, and information quality do not have a significant effect on user satisfaction. In contrast, system quality has a positive and significant effect on user satisfaction. Conclusions:. Conclusions: These findings suggest that, in the context of a mandatory system, technical aspects, such as system reliability, stability, and response speed, play a crucial role in enhancing user satisfaction. Limitations:. Limitations: This study is limited by its narrow scope, limited variables, and reliance on questionnaire data, which may introduce subjectivity. Therefore, improving system quality and providing continuous training are recommended. Contribution:. This study contributes to the development of an integrated model combining the technology acceptance model (TAM) and the DeLone and McLean information systems success model within the context of village government information systems